Retrospective analysis of prognostic factors in patients with duodenal adenocarcinoma - Téoule, Patrick; Gaiser, Timo; Rückert, Felix; Wilhelm, Torsten (European surgery, 2016)
Background: Sporadic duodenal cancer is a rare cancer entity. Therefore, the prognostic significance of clinicopathologic features is unknown. This study aimed to identify prognostic factors and compare survival with other tumour entities of the same anatomical region. Methods: We retrospectively studied medical records of 22 patients with duodenal adenocarcinoma (DAC), who underwent resection in two German centres for pancreatic surgery (1994-2012). Mean time of follow-up was 51.3 months. Predictive factors were evaluated by log rank analysis. Results: Whipple surgery was performed in seven cases (31.8 %), pylorus preserving pancreaticoduodenectomy in 14 cases (63.6 %) and partial duodenectomy in one case (4.5 %). R0-resection was achieved in 86.4 %. In all, 50% of our patients had nodal positive disease. Overall morbidity was 59.1 % and perioperative mortality was 9.1 %. Survival after resection was 63.6 % and 59.0 % (3- and 5-years). There was no significant survival difference between patients with DAC and ampullary cancer, but survival was longer compared with patients with pancreatic cancer. Conclusions: Mortality seems to be high after resection of DAC. However, radical surgery should be performed due to the high number of patients with nodal positive disease. No definite prognostic factors were identified. The prognosis after resection of duodenal cancer can be compared with patients with ampullary cancer.